A Study of Feminism Exploration in Society and Style in Select Novels of Toni Morrison: Examining the Feminist Position in Toni Morrison's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In addition to the Euro-Americans' and the Afro-Americans' shared experiences, women have also had experiences and shared memories” that are exclusively theirs. Consequently, a body of writings emerged decrying the thwarting of the personhood of women in American society. This focus is often referred to as the feminist position. The feminist position is clear it is an attempt to inspire women to become more aware of them and to find a more inclusive niche in a society that has denied them an expansive place. This position among white American women writers is well documented in the literature. Nevertheless, within this vast body of literature by and about white American women, Afro-American women are all too often simply mentioned in passing. So the discussion of the feminist position in this study will be skewed toward the Afro-American woman, for the criticism reveals that this is the feminist position Toni Morrison is concerned with. That is to say, the experiences of black women in America have been vastly different from those of white women in America. In fact, even white women in America have not acknowledged the full personhood of Afro-American women.